Pembentukan Kementerian Pelindungan Pekerja Migran Indonesia dan Masa Depan Perlindungan Pekerja Migran Indonesia - Minan, Ahsanul; Ahsanul Minan; Kartini Laras Makmur (Prodi Ilmu Hukum Universitas Nahdlatul Ulama Indonesia, 2025)
This study analyzes the institutional transformation of migrant worker protection in Indonesia through the establishment of the Ministry of Protection of Indonesian Migrant Workers (KP2MI) under Presidential Regulations No. 165 and 166 of 2024. The research applies historical institutionalism and legal institutionalism approaches to examine the interaction between the historical evolution of policies and law as a normative institution. The findings reveal that the establishment of KP2MI represents a critical juncture in Indonesia’s labor migration governance reform. The shift from an agency to a ministry signifies a transition from a coordinative to an executorial protection paradigm. However, the institution’s effectiveness remains constrained by bureaucratic path dependence, overlapping ministerial authorities, and the lack of legal and service integration. The study concludes that KP2MI’s success depends on strengthening its legal foundation, cross-sectoral coordination, and the implementation of a human-centered and accountable governance model. It recommends reforming the legal framework, digitizing protection systems, and enhancing public participation as the pillars of a just and effective institutional protection mechanism for migrant workers.